2019
DOI: 10.21009/jpud.132.07
|View full text |Cite
|
Sign up to set email alerts
|

Early Childhood Learning Quality in Pandalungan Community

Abstract: The challenge for rural communities to provide quality education for early childhood in Indonesia is difficult. National politics, policies, and economic and cultural conditions affect the Early Childhood Education system, and Indonesia is a large multicultural country, so, even the quality of education is difficult. This study aims to look at the quality of children's education in Pandalungan. Using qualitative methods with ethnographic design, data collection techniques using interviews, observation, and doc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Figures 5 and 6 shows the results of the functional testing survey completed by the respondents. The highest number (5) indicates that they strongly agree, while the lowest (1) indicates that they strongly disagree. Based on Figure 5, 80% of the respondents strongly agree that the application buttons and menus are functional to perform the tasks and produce the desired output while only 10% agrees and another 10% are neutral with their answer.…”
Section: Functionality Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Figures 5 and 6 shows the results of the functional testing survey completed by the respondents. The highest number (5) indicates that they strongly agree, while the lowest (1) indicates that they strongly disagree. Based on Figure 5, 80% of the respondents strongly agree that the application buttons and menus are functional to perform the tasks and produce the desired output while only 10% agrees and another 10% are neutral with their answer.…”
Section: Functionality Testingmentioning
confidence: 99%
“…Studies have suggested that quality of an early childhood learning needs to be addressed as an effort to stimulate and guide a child's thinking ability and skills [4]. Furthermore, it is said that the standards of an early childhood learning can be enhanced using modern technology [5], [6]. The usage of technology in an early childhood learning process may result in creating an explosive thirst for knowledge [7], and increase a child's focus on understanding concepts [8], [9].…”
Section: Introductionmentioning
confidence: 99%
“…The study focused on using origami paper as an instructional tool to enhance the creative abilities of children enrolled in the YALC Pasuruan Kindergarten's Group B, specifically the art and creativity center group. (Nur Atika et al, 2019) Asserts that the centre's establishment encompasses various aspects such as teacher training, setting organization, play initiation, engagement during play, clean-up procedures, and reflection on the experience.…”
Section: Figure 2 Octopus Mediamentioning
confidence: 99%